Comprehensive Approach of Hospital Role in Managing Non-Comunicable Disease - Lutfi Afifudin; Elsye Maria Rosa (Eduvest - Journal of Universal Studies, 2025)
Health problems classified as non-communicable diseases (NCDs) are those that cannot be spread from one person to another directly. With 41 million fatalities annually, or 71 percent of all deaths globally, these illnesses rank as the leading cause of death and disability worldwide. 15 million individuals between the ages of 30 and 69 die from non-communicable diseases (NCDs). The most common cause of NCD fatalities is cardiovascular disease, which is followed by cancer, respiratory conditions, and diabetes. Hospitals are crucial to the management of non-communicable diseases (NCDs) in a number of ways, including palliative care, treatment, screening, and detection. The purpose of this study is to examine hospitals' involvement in NCD management. The scoping review technique, a methodical approach and selection procedure, is employed in this study. The last ten years' worth of publications from national and international databases, including PubMed, Scopus, and Ebsco/Springer, are searched for literature sources. According to the study's findings, hospitals, as health service institutions, play a part in global health diplomacy (GHD), or a negotiated process of collective action for global health. This includes three types of diplomacy: informal diplomacy, which takes the form of interactions between international public health actors and their partners, such as officials from the host country, non-governmental organizations, private businesses, and the community, and core diplomacy, which takes the form of formal negotiations between countries. Multi-stakeholder diplomacy is defined as talks between countries and other actors that don't always result in agreement.